Implementasi Metode Performance-Based Asset Management Dalam Sistem Informasi Manajemen Aset Sekolah (SIMAS) - Ritonga, Nola Putri; Irawan, Muhammad Dedi (Insect (Informatics and Security): Jurnal Teknik Informatika, 2025)
School assets play a vital role in supporting learning activities and administrative operations, yet many schools still manage assets manually, leading to data inaccuracy, difficulty in monitoring conditions, and inefficiency in reporting. This study aims to design and implement a School Asset Management Information System (SIMAS) using the Performance-Based Asset Management (PBAM) method to address these challenges. The research applies a qualitative approach through observation, interviews, and literature study to identify asset management problems in schools. The system was developed using the Waterfall model, consisting of analysis, design, implementation, testing, and documentation. PBAM principles were integrated to support planning, maintenance, monitoring, and continuous improvement of asset utilization. The results demonstrate that SIMAS provides structured asset registration, facilitates real-time monitoring, generates performance-based reports, and issues automatic notifications for urgent maintenance. This contributes to improving decision-making, enhancing efficiency in school asset management, and ensuring long-term sustainability of educational resources. The findings highlight that the application of PBAM in the education sector, particularly in schools, provides a novel contribution compared to previous studies that mainly focused on asset recording and depreciation methods